Korelasi Pemberian Jus Apel dengan Penurunan Respon Nyeri pada Penderita Asam Urat - Sylvie Puspita; Facrur Rozi (Journal of Bionursing, 2021)
Gouty arthritis is a disease that continues to cause pain and tenderness due to deposits of monosodium crystals that accumulate in the joints. Regular consumption of apple juice can decrease pain response by decreasing pain intensity and impulses. The purpose of this study was to analyze the relationship between consumption of apple juice and a decrease in pain response in patients with gout arthritis in the Kebonsari Public Health Center, Pasuruan City. This research is a non-experimental quantitative study using a descriptive study with a cross sectional approach. The population of this study were all patients with gout who went to the health center as many as 60 patients. The sampling technique in this study was consecutiv sampling, totaling 60 respondents. The instrument used to examine pain response and juice consumption was an observation sheet. From the data collected, then testing using sperm rank. The results obtained indicate that based on the test value of 0.000 (ρ <0.05) in H1 is accepted. This means that there is a relationship between consumption of apple juice with a decrease in pain response in patients with gout. Lifestyle changes for gout sufferers are needed to reverse uric acid levels in the blood.